Paleohistology of the Cretaceous resin‐producing conifer Geinitzia reichenbachii using X‐ray synchrotron microtomography. Issue 9 (8th September 2021) - Moreau, Jean‐David; Philippe, Marc; Néraudeau, Didier; Dépré, Eric; Le Couls, Matthieu; Fernandez, Vincent; Beurel, Simon
Abstract: Premise: The conifer Geinitzia reichenbachii was a common member of the Cretaceous Laurasian floras. However, the histology of G. reichenbachii leafy axes was never described in detail, and our knowledge of its paleoecology remains very limited. Using new and exquisitely preserved silicified material from the Upper Cretaceous of western France, we describe G. reichenbachii from the gross morphology to the cellular scale, then discuss paleoecological and taphonomical implications. Methods: We examined specimens from two localities in western France (Claix and Moragne) using propagation phase‐contrast X‐ray synchrotron microtomography. Results: The cuticle and the inner tissues of leafy axes are preserved in three dimensions. Epidermis, hypodermis, palisade parenchyma, spongy parenchyma, transfusion tracheids, and most of tissues of the vascular cylinder are clearly discernible. The numerous resin ducts are sometimes filled by persisting resin. Additionally, surfaces of some leaves preserved drops and flows of resin. Conclusions: Depositional environmental context combined with histological features of G. reichenbachii suggest that this conifer was adapted to a range of marginal‐littoral ecosystems including those open to the sea paleoenvironments and innermost ones influenced by strong continental inputs. Geinitzia reichenbachii was adapted to withstand intense sunlight, hot temperatures coupled with salty sea wind, and dry conditions. The frequent amber‐bearing beds in the Cretaceous from western France with Geinitzia as a main component of the associated floras raises the possibility of a role for Geinitzia in the production of the "Charentese amber".